How do children with bilateral spastic cerebral palsy manage walking on inclines? - Yılmaz Topçuoğlu, Miray-Su; Krautwurst, Britta; Klotz, Matthias C. M.; Dreher, Thomas; Wolf, Sebastian Immanuel (Gait & posture, 2018)
Background - Walking on inclined surfaces is an everyday task, which challenges stability and propulsion even in healthy adults. Children with cerebral palsy adapt similarly to inclines like healthy children do. However, how stability and propulsion in these subjects are influenced by different inclines remained unaddressed as of yet. - Research question - The aim was to examine the feeling of safety, stability and propulsion of children with cerebral palsy when walking on inclines to gain insight into the challenges they might face on these conditions. - Methods - Eighteen children with bilateral spastic cerebral palsy with gross motor function classification scale level I and II and nineteen healthy children underwent instrumented 3D gait analysis on level ground and on a 5° and a 10° incline. A mixed linear model was used to draw between and within group comparisons. - Results - Reduced lateral trunk sway, a relative lengthening of the lower limb at initial contact and a controlled walking speed were employed during downhill gait compared to level walking. Patients showed an increased sagittal ROM of trunk (3-4°) and pelvis (2-3°) and a decreased sagittal knee ROM (13°) compared to the typically developed children. During uphill gait, an insufficient increase of push-off power at the ankle (increase by 0.48 W/kg) was noted in children with CP, which appeared to lead to particularly shorter strides (about 0.1 m) in patients compared to healthy children (increase by 1.32 W/kg). - Significance - Depending on inclination angle, children with cerebral palsy managed to walk on inclines in a controlled manner. The steeper the incline, the more the gait appeared to be affected: decreased feeling of safety, increased need for stabilising mechanisms for downhill gait and less sufficient uphill propulsion were seen. Helping these patients to attain better control during downhill gait and strengthening uphill gait mechanisms may support their participation in everyday life.